Shadowlands : fear and freedom at the Oregon standoff - McCann, Anthony (Bloomsbury Publishing, 2019)
In 2016, a group of armed, divinely inspired right-wing protestors led by Ammon Bundy occupied the Malheur National Wildlife Refuge in the high desert of eastern Oregon. Encamped in the shadowlands of the republic, insisting that the Federal government had no right to own public land, the occupiers were seen by a divided country as either dangerous extremists dressed up as cowboys, or as heroes insisting on restoring the rule of the Constitution. From the Occupation's beginnings, to the trials of the occupiers in federal court in downtown Portland and their tumultuous aftermaths, Shadowlands is the resonant, multifaceted story of one of the most dramatic flashpoints in the year that gave us Donald Trump. Sharing the expansive stage with the occupiers are a host of others -- Native American tribal leaders, public-lands ranchers, militia members, environmentalists, federal defense attorneys, and Black Lives Matter activists -- each contending in their different ways with the meaning of the American promise of Liberty. Gathering into its vortex the realities of social media technology, history, religion, race, and the environment -- this piercing work by Anthony McCann offers us a combination of beautiful writing and high-stakes analysis of our current cultural and political moment. Shadowlands is a clarifying, exhilarating story of a nation facing an uncertain future and a murky past in a time of great collective reckoning.